Ethogram of the free ranging Nasalis larvatus in Bako National Park, Sarawak - Kombi, M.; Abdullah, M.T (Malayan Nature Journal, 2013)
An ethogram on the behaviour and daily activities of the Nasalis larvatus (Proboscis Monkey) provided, based on the field observation conducted in Bako National Park, Sarawak, from December 2011 until December 2012. There were seven categories of behavior successfully described, comprising various activities and movement patterns. They are feeding, resting, agonistic, grooming, solicitation, copulation and locomotion. These categories are then break down in several characteristic activities and actions, such as, jumping, leaping, quadrupedal walking, chasing, slapping, biting, facial threats, postural threats, grooming, solicitation, copulation and others miscellaneous behavior. The most frequently observed behavior recorded during the observation are feeding, travelling and resting. The ethogram and behavioural data provided have improved ourstanding on the behavioural patterns of the N. larvatus in Bako National Park.